The effect of cold water immersion on arm muscle strength in the basketball teamThe effect of cold water immersion on arm muscle strength in the basketball team - Rizki Ramadhan; Prisca Widiawati; Muhammad Putra Ramadhan (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
The goal of this study is to determine the effect of cold water immersion on the arm muscle strength of the basketball team at SMA Negeri 3 of Malang City. This research utilizes an experimental study method. The design used in this research is the "One-group pretest-posttest design”. The results of the study show that the pretest results for the arm muscle strength of the female's basketball team indicate an average arm muscle strength score of 14.33 for the pull test and 15.50 for the push test, whereas the posttest results for arm muscle strength become 14.33 for the pull test and 15.66 for the push test. The significance values obtained are 1.000 for the pull test and 0.802 for the push test. Meanwhile, the results for the male's basketball team indicate that the pretest results for arm muscle strength show an average arm muscle strength score of 20.33 for the pull test and 24.16 for the push test, while the posttest results become 22.16 for the pull test and 25.91 for the push test. The significance values obtained are 0.042 for the pull test and 0.006 for the push test. Thus, it can be concluded that there is no effect of recovery using cold water immersion on the arm muscle strength of the female’s basketball team at SMA Negeri 3 of Malang City, but there is an effect of recovery using cold water immersion on the arm muscle strength of the male’s basketball team at SMA Negeri 3 of Malang City.